Co-design with affect stories and applied ethics for health technologies - Davat, Ambre; Martin-Juchat, Fabienne; Ménissier, Thierry (Frontiers in Communication, 2024)
The integration of digital health technologies in clinical practices and everyday lives of patients raises several issues. Some of them are related to applied ethics. Co-design with patients and, more generally, participatory approaches are increasingly seen as a way to tackle these issues early in the innovation process. This opens the way to an “ethics by co-design”. In this article, we will present the high ambitions of this approach and discuss three challenges raised by ethics by co-design. We will argue that a co-design approach based on affect stories is a way to address these challenges. Then we will focus on a concrete example of a European research project, to discuss the gap between these ethical and theoretical ambitions and what can be achieved in practice. This project aimed at developing an implantable connected device for the monitoring of heart failure, while addressing the ethical, legal and social issues raised by this new technology. However, co-design with patient representatives was in fact limited to a small part of the project: the design of an information module. Based on 18 meetings with a team of 4 patient partners, and 26 additional interviews with patients, we were able to better understand patients’ experiences and priorities in terms of ethics. Together, we co-designed an information module that embodies a vision of the device negotiated between the patients and the technology designers.